Cerebral hemodynamic reactivity measured by near-infrared spectroscopy in migraineurs. - Akin, A; Emir, U; Bolay, H (2005)
Brain hemodynamic responses (BHR) of healthy subjects and migraineurs performing a breath holding task are measured by functional near-infrared spectroscopy (fNIRS) method. The response curves are deconvolved from a rectangular input function to yield the impulse response (IR) function of BHR which was then modeled by a summation of three gaussians. Our results show that the amplitude coefand#163;cients estimated from IR of BHRs are approximately 350% and the dispersion coefand#163;cients 145% higher for healthy subjects. These results conand#163;rm the and#163;ndings of several other researchers where a decrease in cerebral blood and#164;ow has been shown for migraineurs during breath holding tasks.